Mir-485-5p on the Morphology and Function of Cardiovascular System - Zhang, Delai; Nie, Qian; Liu, Yanru; Li, Zaoying; Xie, Wen; Jiang, Li (Cellular and Molecular Biology, 2022)
Cardiovascular disease is a global problem that seriously endangers human health and life. At present, hypertension is considered to be a polygenic disease caused by the interaction of environmental factors and genetic factors. Various environmental factors have been proved to promote the occurrence and development of cardiovascular disease. MicroRNA (miR), as an essential gene regulatory factor in vivo, has been confirmed to participate in the regulation of many cell pathways, and its abnormal expression is closely related to a variety of human diseases. MiR-485-5p is located at 7q22.1, which has been proved to play an essential role in the tumor and cardiovascular system. Therefore, this paper discussed the mechanism of miR-485-5p on the morphology and function of the cardiovascular system. It is believed that miR-485-5p will impact the morphology and function of the cardiovascular system. Therefore, in the current study, 1655 unrelated patients with cardiovascular system diseases were simulated and analyzed based on the above background. A double luciferase reporter gene detection system verified the combination of miRNAs target recognition. The results showed that miR-485-5p significantly inhibited the luciferase activity of pGL-miR-wt but had no effect on pGL6-miR-mut. The lack of miR-485-5p can promote the activation of cardiac fibroblasts. The findings of this study can provide a new understanding and direction for the study of cardiovascular system morphology and function.